The status of sunnah in Islam - Hamad Alfarisi, Hamad Abdulsalam; Osmani, Noor Mohammad; Zubi, Zainab (Human Resource Management Academic Research Society (HRMARS), 2023)
In Islam, the Sunnah of the Prophet Muhammad (PBUH) has a very high-standing status. The Sunnah derived its place from the authority of revelation. The sunnah is a part of the revelation and preserved to explain the Quran and to guide Muslims. The authority of the Holy Quran and the sunnah of the Holy Prophet (PBUH) was never denied by any jurist. It is a matter of agreement and consensus among Muslim scholars that the revelation is in two parts, the first part is the Quran, and the second part is the Sunnah of the Prophet (PBUH) and it is this part which is explaining what Allah want from us. Accepting the Prophet’s decisions and rulings are part of Muslim’s faith. Accordingly, this short review aims to highlight the status of Sunnah in Islam by reviewing the available relevant literature. The review showed that Sunnah is located in the heart of Usul-Alfiqh, Al-Fiqh, Quranic sciences, and it is the second source of Islamic law. Further detailed researches are recommended to show how Sunnah is relevant to all aspects of human life.